A Longitudinal Study of the Human Oropharynx Microbiota Over Time Reveals a Common Core and Significant Variations With Self-Reported Disease - Bach, Lydia Luise; Ram, Asha; Ijaz, Umer Z.; Evans, Thomas J.; Lindström, Jan (Frontiers in Microbiology, 2021)
Our understanding of human microbial communities, in particular in regard to diseases is advancing, yet the basic understanding of the microbiome in healthy subjects over time remains limited. The oropharynx is a key target for colonization by several important human pathogens. To understand how the oropharyngeal microbiome might limit infections, and how intercurrent infections might be associated with its composition, we characterized the oropharyngeal microbiome of 18 healthy adults, sampled weekly over a 40-weeks using culture-independent molecular techniques. We detected nine phyla, 202 genera and 1438 assignments on OTU level, dominated by Firmicutes, Bacteroidetes and Proteobacteria on phylum level. Individual microbiomes of participants were characterized by levels of high alpha diversity (mean=204.55 OTUs, sd=35.64), evenness (19.83, sd=9.74) and high temporal stability (mean Pearson’s correlation between samples of 0.52, sd=0.060), with greater differences in microbiome community composition between than within individuals. Significant changes in community composition were associated with disease states, suggesting that it is possible to detect specific changes in OTU abundance and community composition during illness. We defined the common core microbiota by varying occurrence and abundance thresholds showing that individual core microbiomes share a substantial number of OTUs across participants, chiefly Streptococci and Veillonella. Our results provide insights into the microbial communities that characterize the healthy human oropharynx, community structure and variability, and provide new approaches to define individual and shared cores. The wider implications of this result include the potential for modelling the general dynamics of oropharynx microbiota both in health and in response to antimicrobial treatments or probiotics.